2000
DOI: 10.1115/1.1338119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Procedures for Irradiation Effects and Sodium Environmental Effects for the Structural Design of Japanese Fast Breeder Reactors

Abstract: In the structural design of fast breeder reactors, irradiation effects and sodium environmental effects on structural materials have to be taken into account. In this paper, firstly, an evaluation procedure for irradiation effects on the mechanical properties of 316FR (FBR Grade 316 stainless steel), which is a newly developed stainless steel for the Japanese demonstration fast breeder reactor, is proposed. The procedure gives a limit of accumulated fast neutron fluence E>0.1 MeV as a function of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Furukawa et al (1998) reported tensile data on 316FR pre-exposed to sodium, and creep, fatigue, and creep-fatigue results on 316FR in flowing sodium. It was found that tensile properties of 316FR were not affected by sodium exposure at 500-550°C for 5000 h. Creep rupture tests conducted at 550-600°C in September 15, 2008 60 flowing sodium at the oxygen level of 1 ppm showed that creep rupture strength in sodium was slightly lower than that in air with predominant surface grain boundary cracking when the rupture time was between 1000 and 10,000 h; at the lower stress level and longer rupture time, sodium exposure had no influence on the creep rupture strength of 316FR, as shown in Figure 4.59 (Asayama et al 2001). …”
Section: Effects Of Sodium Exposurementioning
confidence: 96%
See 4 more Smart Citations
“…Furukawa et al (1998) reported tensile data on 316FR pre-exposed to sodium, and creep, fatigue, and creep-fatigue results on 316FR in flowing sodium. It was found that tensile properties of 316FR were not affected by sodium exposure at 500-550°C for 5000 h. Creep rupture tests conducted at 550-600°C in September 15, 2008 60 flowing sodium at the oxygen level of 1 ppm showed that creep rupture strength in sodium was slightly lower than that in air with predominant surface grain boundary cracking when the rupture time was between 1000 and 10,000 h; at the lower stress level and longer rupture time, sodium exposure had no influence on the creep rupture strength of 316FR, as shown in Figure 4.59 (Asayama et al 2001). …”
Section: Effects Of Sodium Exposurementioning
confidence: 96%
“…316LN-IG has higher allowable stresses than typical 316LN due to an optimal combination of the alloying elements such as carbon, nitrogen, nickel, chromium, manganese and molybdenum, with a tight specification of their allowable composition range. A comprehensive database has been established on 316LN-IG, including heat-to-heat variations, the effect of product size, fracture toughness, effects of neutron irradiation, etc., and the data can be found in the ITER Materials Properties Handbook ( The chemical compositions of 316LN, 316LN-IG, and 316FR stainless steels are given in Table 4-11 (Asayama 2001, Tavassoli 1995, Brinkman 2001. Significant data base of tensile, creep, fatigue and creep-fatigue properties of 316FR and 316LN base metal and weld metal can be found in the RCC-MR, ITER MPH and open literature.…”
Section: Fr and 316ln Stainless Steelsmentioning
confidence: 99%
See 3 more Smart Citations